Compression Molded Kenaf/Polypropylene (K/PP) Composite : Determination Of Impact Properties Using Design Of Experiment (DOE) Analysis - Loh, Xiao Hui (2017)
Natural fiber is an attractive replacement material for synthetic fiber as it owns countless advantages outlined by researchers. Industry field is adopting natural fiber as application where matching them with suitable polymer. In this study, kenaf/polypylene (K/PP) composite will be tested on Izod impact strength (ASTM D256) by varying fiber weight and length and subjected under various impact angles. Maleic anhydride-grafted-polypropylene (MAPP) will be premixed with polypropylene (PP) using internal mixer to enhance surface contact between fiber and matrix. Hardness and density test will also be conducted to identify physical properties of samples. Microstructure observation will be carried out to visualize bonding surface between fiber and matrix. Next, design of experiment (DOE) analysis will be used to identify the relationship between these factors outlined. From Izod impact test outcome, higher fiber length did helps to improve impact properties of composite as well. But, stress distribution of fiber at shorter length at lower impact angle is more significant. Therefore, sample with fiber length 1 cm and loading 30 wt.%was determined as best sample which can present good impact properties at different impact angles. Microstructure of sample shows fiber has good surface coverage with addition of MAPP into PP. Lastly; prediction of impact behavior for K/PP composite can be done by applying formula obtained through factorial analysis generated by Minitab software.